ADAPTATION STRESS LEVEL RESPONSE OF NEW STUDENTS IN BOARDING SCHOOLS - Abdul Ghofar,; Tisa Fatichul Hanif,; M Zulfikar Asumta,; Wim Banu Ukhrowi, (International Journal of Social Science, 2022)
Stress is a part of human life. Humans will never escape the experience of feeling tension in their life. Stress arises in line with the events and journeys of life that are passed by individuals and their occurrence cannot be completely avoided. In this study, new students in male and female dormitories must enter a new environment so that separate problems will arise for these individuals due to differences in the physical and social environment.Objective:This study aims to describe the response to the level of adaptation stress, identify the level of adaptation stress, and find out the symptoms of adaptation stress in new students in male and female dormitories.Method:used in this research is descriptive quantitative. The population in this study were all new students in the male and female dormitories, with a sample of 107 students. The instrument used in this study was a questionnaire with a guttman scale and a structured questionnaire consisting of 15 questions.Results:Based on the results of data processing, the level of stress experienced by students based on gender shows that female students are more easily stressed and students aged 15-17 years or equivalent to junior high school education also experience stress easily.. Discussion:Based on the results of data processing, stress levels are classified into three, namely mild 33.6%, moderate 53.3%, severe 13.1%. The highest adaptation stress level response for new students was in the moderate stress category with symptoms such as dizziness, irritability, anxiety or anxiety, unstable mood, decreased appetite, frequent daydreaming, loss of trust in others.